2002
DOI: 10.5194/angeo-20-213-2002
|View full text |Cite
|
Sign up to set email alerts
|

Aspect sensitivity measurements of polar mesosphere summer echoes using coherent radar imaging

Abstract: Abstract. The Esrange VHF radar (ESRAD), located in northern Sweden (67.88 • N, 21.10 • E), has been used to investigate polar mesosphere summer echoes (PMSE). During July and August of 1998, coherent radar imaging (CRI) was used to study the dynamic evolution of PMSE with high temporal and spatial resolution. A CRI analysis provides an estimate of the angular brightness distribution within the radar's probing volume. The brightness distribution is directly related to the radar reflectivity. Consequently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 53 publications
5
40
2
Order By: Relevance
“…A similar height dependence of PMSE aspect sensitivity has been reported in other studies (Czechowsky et al, 1988;Zecha et al, 2001;Chilson et al, 2002). Long-term aspect sensitivity measurements of PMSE at Resolute Bay by Swarnalingam et al (2011) revealed that, for strong and moderate PMSE, the median aspect angles at 84 km are by 2-4 • smaller than those at 88 km.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…A similar height dependence of PMSE aspect sensitivity has been reported in other studies (Czechowsky et al, 1988;Zecha et al, 2001;Chilson et al, 2002). Long-term aspect sensitivity measurements of PMSE at Resolute Bay by Swarnalingam et al (2011) revealed that, for strong and moderate PMSE, the median aspect angles at 84 km are by 2-4 • smaller than those at 88 km.…”
Section: Discussionsupporting
confidence: 60%
“…These show that turbulence occurrence rates start to grow from 80 km and maximise at about 88 km (Rapp and by Lübken, 2003). Chilson et al (2002) and Zecha et al (2001) noticed the enhanced aspect sensitivity at the lower edges of PMSE sublayers. Similar features are seen in our Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations